Why Funding is not a Solution to the "Social Security Crisis" - Friedrich Breyer (Deutsches Institut für Wirtschaftsforschung (DIW), 2001)
It is now a commonplace that the unfunded public pension systems of many OECD countries will run into severe financing problems in the coming decades due to a dramatically increasing pensioner/worker ratio. While this diagnosis is completely undisputed, there is still a vigorous debate on the appropriate therapy. In this debate, a number of proposals have been brought forward in particular in the last five years, which mainly consist in a (partial) transition to a funded pension system. Because such a transition is not a Pareto improvement, it is necessary to ask what can be the policy target that justifies such a redistributive move? The present paper tries to examine this question by identifying seven fallacies that are commonly made by advocates of such a transition. – – Es ist heute unbestritten, dass die umlagefinanzierten staatlichen Rentensysteme in den meisten OECD.Ländern in den kommenden Jahrzehnten wegen der dramatisch steigenden Alterslastquote schwerwiegende finanzielle Probleme bekommen werden. Dennoch gibt es eine intensive Debatte über die angemessene Therapie. Gerade in den letzten Jahren haben Vorschläge zugenommen, die auf einen (teilweisen) Übergang zur Kapitaldeckung hinauslaufen. Da ein solcher Übergang bekanntlich keine Pareto-Verbesserung bewirkt, muss man fragen, durch welche Zielsetzungen er gerechtfertigt werden könnte. Die vorliegende Arbeit geht dieser Frage nach und identifiziert sieben Trugschlüsse, die von Anhängern eines solchen Übergangs häufig begangen werden.
Keywords: 330; Gesetzliche Rentenversicherung; Kapitaldeckungsverfahren; Pareto-Optimum; Kritik; Theorie